Karya Tari “Kabakato” Penafsiran Bentuk Komunikasi Dari Tradisi Alu Katentong Di Nagari Padang Laweh Kecamatan Sungai Tarab Kabupaten Tanah Datar - A’in, Nurul; Rovylendes, Adjuoktoza; Syahril; Putra, Ariefin Alham Jaya (JURNAL ILMIAH NUSANTARA, 2025)
The dance work "KabaKato" is inspired by the traditional art of Alu Katentong, which is found in Nagari Padang Laweh, Sungai Tarab District, Tanah Datar Regency. This traditional art is performed by women as a means of communication in the community to signal the occurrence of traditional ceremonies, such as weddings, turun mandi (baby's first bath), batagak pangulu (traditional leadership ceremony), and the construction of Rumah Gadang (traditional house). Based on this phenomenon, the choreographer translates it into a group choreography that is performed at the Adam Auditorium of the Indonesian Institute of Arts in Padangpanjang. This work is divided into three parts and is performed by ten dancers. The makeup and costume used are stage makeup for male dancers, while the costume used is a kuruang shirt and loose pants, and a creative taluaak balango shirt for men. The method used in creating this work is data collection or field observation, data processing, literature study, exploration, movement arrangement, improvisation, formation, and evaluation.